The Relevance of Islamic Law and Positive Law in State Safety Management: Literacy Study of Islam and National Law - Suleman, Zulkarnain; Suleman, Zulfitri Zulkarnain (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
The obedience of citizens to every legal product, such as state law and Islamic law for its adherents, is absolute when a country and religious people want to create a democratic climate in the 21st century. This study discusses the governance of citizens’ compliance with the law, especially Islamic law, in a Pancasila-democratic country. There are two sources of law in Indonesia; the first is religious law and positive state law, both of which invite people to the path of goodness for justice and democracy. This study uses a phenomenological approach to collect as much data as possible and examine it to obtain relevant answers. This study concludes that the governance of citizens’ compliance with Islamic law in a democratic country is mutually supportive obedience, meaning that they obey religion, so they will abide by the state so that this country becomes a democratic country. Ketaatan warga negara terhadap setiap produk hukum seperti hukum negara dan hukum Islam bagi pemeluknya adalah mutlak ketika sebuah negara dan umat beragama ingin menciptakan iklim demokrasi di abad 21. Penelitian ini ingin membahas tata kelola kepatuhan warga negara terhadap hukum, khususnya hukum Islam, di negara demokrasi Pancasila. Ada dua sumber hukum di Indonesia; yang pertama adalah hukum agama dan hukum positif negara, keduanya mengajak masyarakat ke jalan kebaikan untuk keadilan dan demokrasi. Penelitian ini menggunakan pendekatan fenomenologis untuk mengumpulkan data sebanyak mungkin dan memeriksanya untuk mendapatkan jawaban yang relevan. Penelitian ini menyimpulkan bahwa tata kelola kepatuhan warga negara terhadap hukum Islam di negara demokrasi adalah kepatuhan yang saling mendukung, artinya mereka mematuhi agama, sehingga mereka akan mematuhi negara sehingga negara ini menjadi negara demokrasi